An update on chemical pharmacotherapy options for the prevention of kidney transplant rejection with a focus on costimulation blockade - Kälble, Florian; Schaier, Matthias; Schäfer, Sebastian Markus; Süsal, Caner; Zeier, Martin; Sommerer, Claudia; Morath, Christian (Expert opinion on pharmacotherapy, 2017)
Introduction: The introduction of calcineurin inhibitors (CNI) has greatly improved graft survival in the past three decades. However, long-term graft survival is still limited due to chronic allograft injury and side-effects of immunosuppressive medication. Areas covered: The present overview gives an update on pharmacotherapeutic strategies after kidney transplantation. The main focus is on CNI-sparing regimens using co-stimulatory blockade and on new substances on the horizone. Expert opinion: CNI sparing regimens are well-established. Complete CNI avoidance after kidney transplantation was often associated with impaired graft survival until the approval of the co-stimulation blocker belatacept for de novo immunosuppression after kidney transplantation. Concerns still exist with respect to severe T-cell-mediated rejection episodes in the early phase after transplantation. Thus, a triple drug regimen with CNI, mycophenolic acid and steroids still represents the gold-standard of immunosuppressive therapy. Alternative substances expand the possibilities of tailoring individual immunosuppression for different indications such as biopsy-proven CNI toxicity, polyoma virus BK nephropathy or CNI-triggered thrombotic microangiopathy. However, a change of the immunosuppressive therapy must always be balanced against each patient´s individual immunological risk in order to address the importance of chronic antibody-mediated rejection driven by donor specific antibodies (DSA).